Role for Carboxylic Acid Moiety in NSAIDs: Favoring the Binding at Site II of Bovine Serum Albumin - de Carvalho Bertozo, Luiza [UNESP]; Tadeu, Hugo Cesar [UNESP]; Sebastian, Anila; Maszota-Zieleniak, Martyna; Samsonov, Sergey A.; Ximenes, Valdecir Farias [UNESP] (American Chemical Society (ACS), 2024)
The molecular structures of nonsteroidal anti-inflammatory drugs (NSAIDs) vary, but most contain a carboxylic acid functional group (RCOOH). This functional group is known to be related to the mechanism of cyclooxygenase inhibition and also causes side effects, such as gastrointestinal bleeding. This study proposes a new role for RCOOH in NSAIDs: facilitating the interaction at the binding site II of serum albumins. We used bovine serum albumin (BSA) as a model to investigate the interactions with ligands at site II. Using dansyl-proline (DP) as a fluorescent site II marker, we demonstrated that only negatively charged NSAIDs such as ibuprofen (IBP), naproxen (NPX), diflunisal (DFS), and ketoprofen (KTP) can efficiently displace DP from the albumin binding site. We confirmed the importance of RCOO by neutralizing IBP and NPX through esterification, which reduced the displacement of DP. The competition was also monitored by stopped-flow experiments. While IBP and NPX displaced DP in less than 1 s, the ester derivatives were ineffective. We also observed a higher affinity of negatively charged NSAIDs using DFS as a probe and ultrafiltration experiments. Molecular docking simulations showed an essential salt bridge between the positively charged residues Arg409 and Lys413 with RCOO-, consistent with the experimental findings. We performed a ligand dissociation pathway and corresponding energy analysis by applying molecular dynamics. The dissociation of NPX showed a higher free energy barrier than its ester. Apart from BSA, we conducted some experimental studies with human serum albumin, and similar results were obtained, suggesting a general effect for other mammalian serum albumins. Our findings support that the RCOOH moiety affects not only the mechanism of action and side effects but also the pharmacokinetics of NSAIDs.
Keywords: albumin; binding sites; molecular dynamics; NSAIDs; pharmacokinetics